Temporal asymmetries in auditory coding and perception reflect multi-layered nonlinearities - Thomas Deneux (Nature Portfolio, 2016)
In humans, sounds that increase in intensity over time (up-ramp) are perceived as louder than down-ramping sounds. Here the authors show that in mice this bias also exists and is reflected in the complex nonlinearities of auditory cortex activity.